‘Moving the Kaleidoscope’ to see the effect of creative personality traits on creative thinking dispositions of preservice teachers: The mediating effect of creative learning environments and teachers’ creativity fostering behavior - Ayyildiz, Pınar; Yilmaz, Adem (Elsevier BV, 2021)
Abstract This study aimed to examine the effect of creative personality traits on creative thinking dispositions through creative learning environments and teacher behaviors that foster creativity. Gender, department, and grade level are also defined as common variables. 1320 teacher candidates who were selected with purposeful and appropriate sampling supported the research. 726 of these individuals are females and 594 are males. Participants in the study are teacher candidates from education faculties, science, mathematics, classroom, and educational sciences departments. Whilst determining the participants, attention was paid to the selection of those who have previously taken courses that are directly or indirectly related to creative thinking, critical and analytical thinking, entrepreunership and creativity. Descriptive and inferential statistics were used in the analysis of the research data. Aside from this, the mediation effect of variables was performed using Hayes' number 6 serial multiple mediation analysis models. As a result of the research, it was found that creative personality traits positively predicted creative thinking dispositions through the learning environment and teachers' fostering behaviors. The creative learning environment and teachers' fostering behaviors similarly have a positive mediating effect.
Keywords: 4. Education; 10. No inequality; 16. Peace & justice